In-vitro and Ex-vivo Modulatory Effects of Atractylodin and \(β\)-Eudesmol on Human Cytochrome P450 Enzymes - Artitaya Thiengsusuk; Tullayakorn Plengsuriyakarn; Kesara Na-Bangchang (Pharmaceutical Science: New Insights and Developments Vol. 1, 2024)
Background: Atractylodin and \(β\)-eudesmol, the major bioactive compounds in Atractylodes lancea, are promising candidates for anti-cholangiocarcinoma. However, their modulatory effects on cytochrome P450s (CYP450s) remain unclear. Objective: This study aimed to investigate the modulatory effects of two bioactive compounds, atractylodin and \(β\)-eudesmol, derived from Atractylodes lancea, on human cytochrome P450 enzymes (CYP450s), both in vitro and ex vivo, to assess their potential risks in clinical applications, particularly for anti-cholangiocarcinoma therapy. Methods: The inhibitory effects of atractylodin and \(β\)-eudesmol on recombinant human CYP450 enzymes (rCYP1A2, rCYP2C9, rCYP2C19, rCYP2D6, and rCYP3A4) were evaluated using luminogenic CYP450 kits. For the ex vivo analysis, mice were administered daily oral doses of atractylodin or \(β\)-eudesmol (100 mg/kg body weight) for 1, 7, 14, and 21 days. Liver samples were collected at each time point to assess mRNA and protein expression levels of CYP1A2 and CYP3A11 (the mouse equivalent of human CYP3A4) enzymes and their enzyme activities. Results: Both atractylodin and \(β\)-eudesmol showed weak inhibitory effects on all recombinant CYP450 enzymes compared with the reference inhibitors (IC50 values ranging from 167 \(μ\)M to >686 \(μ\)M). However, \(β\)-eudesmol was most potent against rCYP2C19 (IC50 = 172.7 \(μ\)M) and rCYP3A4 (IC50 = 218.6 \(μ\)M). In the ex vivo study, short-term exposure (1-7 days) to these compounds led to upregulating CYP1A2 and CYP3a11 mRNA, protein expression, and enzyme activity. In contrast, prolonged exposure (\(\)14 days) resulted in significant downregulation of these markers, which correlated with decreased enzyme activities, particularly CYP1A2 and CYP3a11. Clinical Implications: These findings highlight potential clinical concerns for using atractylodin and \(β\)-eudesmol in treating cholangiocarcinoma, especially with prolonged dosing. Chronic exposure to these compounds may inhibit CYP3A4 activity, leading to potential toxicity and metabolic interactions with coadministered drugs that rely on CYP3A4 for metabolism. Caution is advised when using these compounds in combination therapies. Conclusion: While atractylodin and \(β\)-eudesmol show promise as anti-cholangiocarcinoma agents, their chronic use may pose risks due to CYP3A4 inhibition and potential drug interactions. Further studies are needed to evaluate their safety profile and therapeutic window in clinical settings.